An overview of case reports and case series of pulmonary actinomycosis mimicking lung cancer: a scoping review - Khoshbayan, Amin; Amirmozafari, Nour; Mirkalantari, Shiva (Frontiers in Medicine, 2024)
Background: Pulmonary Actinomycosis (PA) is a rare type of Actinomyces infection that can be challenging to diagnose since it often imitates lung cancer.Published case reports and case series of PA in patients with suspicion of lung cancer were considered, and data were extracted by a structured search through PubMed/Medline.Results: After analyzing Medline, 31 studies were reviewed, from which 48 cases were extracted. Europe had the highest prevalence of reported cases with 45.1%, followed by Asia (32.2%), America (19.3%), and Africa (3.2%). The average age of patients was 58.9 years, and 75% of all patients were above 50 years old. Males (70%) were predominantly affected by PA. The overall mortality rate was 6.25%. In only 8 cases, the causative agent was reported and Actinomyces odontolyticus was the most common isolated pathogen with 3 cases. Based on histopathological examination, 75% of the cases were diagnosed, and the lobectomy was performed in 10 cases, the most common surgical intervention. In 50% of the cases, the selective antibiotic was intravenous and oral penicillin. Followed by amoxicillin (29.1%), amoxicillinclavulanic acid, ampicillin, levofloxacin, and doxycycline.The non-specific symptoms resemble lung cancer, leading to confusion between PA and cancer in imaging scans. Radiological techniques are helpful but have limitations that can lead to unnecessary surgeries when confusing PA with lung cancer. Therefore, it is important to raise awareness about resemble signs and symptoms of PA and lung cancer to prevent undesirable complications and ensure appropriate treatment measures are taken with awareness.